Comparative Analysis Of The Quality Of Sweet Potato Leaf Chips And Spinach Leaf Chips - Wiyono, Adhytiya Kusumah; Asnur, Lise (Universitas Negeri Padang, 2025)
The purpose of this study was to compare the quality of sweet potato leaf chips and spinach leaf chips through an organoleptic test covering shape, color, texture, aroma, and taste. This study employed a true experimental method with three expert panelists who conducted evaluations three times using a hedonic scale of 1–4 (1 = dislike, 4 = like very much). Since the data were not normally distributed, descriptive analysis was performed and followed by the Wilcoxon Signed Rank test. The results showed that, descriptively, sweet potato leaf chips obtained higher average scores in texture, aroma, and taste compared to spinach leaf chips, with the highest score on the taste attribute (4 = like), indicating a high level of acceptance. However, the Wilcoxon test results revealed no significant differences (p > 0.05) between the two products across all attributes. Therefore, although sweet potato leaf chips had higher mean scores descriptively, statistically there was no significant difference compared to spinach leaf chips. This indicates that both products have an equal level of sensory acceptance, with sweet potato leaf chips demonstrating strong consistency in the taste attribute and potential as an alternative raw material for innovative snacks and food product diversification.